2017
DOI: 10.1063/1.5011639
|View full text |Cite
|
Sign up to set email alerts
|

Transmural remodeling of right ventricular myocardium in response to pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) imposes substantial pressure overload on the right ventricular free wall (RVFW), leading to myofiber hypertrophy and remodeling of its collagen fiber architecture. The transmural nature of these adaptations and their effects on the macroscopic mechanical behavior of the RVFW remain largely unexplored. In the present work, we extended our constitutive model for RVFW myocardium to investigate the transmural mechanical and structural remodeling post-PAH. Recent murine experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 31 publications
9
42
1
Order By: Relevance
“…The G&R model was able to generate the fiber reorientation across the RVFW thickness as seen in the PAH heart (Fig. 8), and also consistent with previous histological studies [10,12]. The fibers exhibited an average reorientation of $16 deg from horizontal (Fig.…”
Section: Structuralsupporting
confidence: 86%
See 2 more Smart Citations
“…The G&R model was able to generate the fiber reorientation across the RVFW thickness as seen in the PAH heart (Fig. 8), and also consistent with previous histological studies [10,12]. The fibers exhibited an average reorientation of $16 deg from horizontal (Fig.…”
Section: Structuralsupporting
confidence: 86%
“…A gradual increase in RV volume with a modest rate as well as slight changes in the fiber structure were also observed. Stiffening has been attributed to multiple mechanisms, including changes in myocyte biophysical properties, such as titin upregulation, changes in the collagen recruitment rate [12], and collagen fibrosis. Similarly, the changes in the RVFW contractility may stem from intrinsic changes in myocyte properties such as alterations in actin/myosin protein isoforms [2] as well as myofiber hypertrophy through sarcomerogenesis.…”
Section: Time-course Behavior Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…While we found a greater increase in circumferential than AOT stress during hypertrophic remodeling in the SuHx rat, AOT stiffness increased more than circumferential stiffness in the PA-banded rat [7,8]. Based on histology and a microstructural constitutive analysis [6], those authors also concluded that the anisotropic changes seen in the PA-banded rat were due to reorientation of myofibers and matrix during hypertrophy.…”
Section: Discussionmentioning
confidence: 50%
“…Our recent analysis of right ventricular hemodynamics in the monocrotaline-treated rat model of PAH [5] showed that, while systolic function remained compensated against increased pulmonary artery pressure by increased RV volume and contractility, there was also a significant increase in end-diastolic myocardial stiffness though chamber compliance was unaltered due to the RV dilation. Previous multi-axial testing studies of RV myocardium (MYO) in small animal models of RV hypertrophy have reported increased myocardial stiffness [6][7][8]. Therefore, we sought to determine whether RV myocardial biaxial mechanical properties were also altered in an animal model of PAH.…”
Section: Introductionmentioning
confidence: 99%